Comparison of the effects of exercise with chondroitin sulfate on knee osteoarthritis in rabbits - Ma, Ning (J Orthop Surg Res, 2018)
BACKGROUND: The aim of the study is to compare the effects of exercise therapy with chondroitin sulfate (CS) therapy in an experimental model of osteoarthritis (OA). METHODS: Twenty-one New Zealand rabbits were randomly divided into four groups: normal group (N group, n = 3); OA control group (C group, n = 6); OA plus medication group (CS group, n = 6); and OA plus exercise group (E group, n = 6). Four weeks after modeling, the rabbits were subjected to exercise (artificial, 30 min/time, 4 times/week) or medicated with CS (2% CS, 0.3 ml/time, once/week) for 4 weeks. Histopathological changes in treated joints were examined after staining. X-ray and scanning electron microscopy was used to evaluate the different therapies by examining the surfaces and joint spaces of the articular cartilage. RT-qPCR was used to assess chondrogenic gene expression including Col2, Col10, mmp-13, il-1β, adamats-5, and acan in the experimental groups. RESULTS: Histology showed both treatment groups resulted in cartilage that was in good condition, with increased numbers of chondrocytes, and the results of X-ray and scanning electron microscopy showed the therapeutic effect of exercise therapy is equivalent to CS therapy, surface articular cartilage was flat, and the of cartilage layer was thinning. All treated groups induced the expression of Col10 and Col2 and decreased expression of mmp-13, il-1β, and adamats-5 compared with the control groups. The expression of acan was upregulated in the E group and downregulated in the CS group. Furthermore, expression of Col10 was higher and il-1β was lower in the exercise group compared to that of the CS group. CONCLUSION: These results indicate that exercise has a positive effect on OA compare with CS, and it also supplies reference for the movement mode to improve function.